Media consumption behaviours and health impacts of video-on-demand services in Indonesia - Hilarius Bambang Winarko; Daniel Susilo (Faculty of Communications Science, Dr. Soetomo University, 2024)
Video-on-demand (VOD) services have transformed media consumption globally, with platforms such as Netflix and local providers like Vidio gaining popularity in Indonesia. This study explores the impact of VOD on user behaviours, demographic influences, and health implications in Indonesia, whereby rapid internet expansion drives its adoption. This study aimed to explore how VOD consumption affects daily habits as well as how binge-watching affects health. This research focuses on Indonesia’s unique context with a survey of 422 respondents to analyse VOD habits, and quantitative statistical methods were applied to assess behavioural patterns based on demographic variables. Findings reveal that younger users are the primary consumers of VOD, often engaging with media during work or study hours, resulting in sleep disruption and mental health concerns such as anxiety. Gender differences were notable, with female respondents reporting higher sleep disturbances. Binge-watching behaviour was strongly correlated with health impacts, emphasising the need for better viewing habits. The study concludes that while VOD has enhanced media access and diversity, it has also introduced health risks, particularly for younger audiences. These findings provide valuable insights for VOD platforms and policymakers aiming to promote balanced media consumption. Future research should examine broader demographic trends and long-term effects.